Development of Local Government Institutional Capacity in Improving the Quality of Integrated Licensing Services in 2022 (Study at the Investment Office and One-Stop Integrated Services of Sumbawa District) - Kariyani, Leni Nurul; Irawansyah, Irawansyah; Waldani, Handri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Institutional capacity development plays an important role in various aspects of existence, one of which is in the realm of government institutions. Capacity building is very important to increase the efficiency and efficacy of officers in carrying out their responsibilities as civil servants. In addition, government policy regulations and deregulation have the potential to hamper the operational performance of organizations in providing their public services. Capacity Development is an activity carried out to develop various strategies to increase the usefulness, effectiveness, quality of services and responsiveness to government performance, as well as increasing individual capabilities and resources to achieve the desired goals and responses, namely how to synchronize needs and abilities for this purpose. The aim of this research is to analyze what factors influence the development of institutional capacity at the Sumbawa Regency Investment and One-Stop Integrated Services Service in improving the quality of licensing services. This research uses a qualitative descriptive method which describes a situation, an object or an event without drawing a general conclusion. Data collection techniques through observation, interviews and documentation. The research results show that there are 2 factors that influence the development of institutional capacity at DPMPTSP Kab. Sumbawa, namely first, supporting factors. First, supporting factors in developing institutional capacity in DPMPTSP Sumbawa Regency are Leadership and Shared Commitment. Second, the inhibiting factors in developing institutional capacity in the Sumbawa Regency DPMPTSP are Budget Capacity and inconsistent regulations.